Haitians in limbo – Legal responses for migration induced by the 2010 Haitian earthquake on the American continent - Horváth, Valéria (Pécs journal of international and European law, 2021)
The way and the extent to which environmental degradation contributes to the most recent migra- tion trends and refugee crises has so far been under researched. It is precisely the multidimensional quality of human security that is not reflected adequately by most immigration laws, which pre- scribe oversimplifying legal categories for the complex circumstantial situations that life on earth produces. Although the Cartagena Declaration on Refugees of 1984 calls for the signatories to add––among other legal grounds––„other circumstances which have seriously disturbed public order”, none of contracting states actually enacted any relevant legislation. This paper collects and reflects on the legal responses to the influx of Haitian migrants following the earthquake in Port-au-Prince, Haiti in January 2010 provided by countries on the American continent.